Influence and types of crimes committed by organized crime in prison the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article the author tries to uncover the manifestation of organized crime in prison and the level of their negative impact in the prison system. In this regard, the author examines the unwritten laws of convicted criminal subculture, and the types of crimes committed by organized criminal groups referring to materials conducted by the author in 2014 with the prisoners who are members of an organized criminal group in the prisons of the South Kazakhstan and Kyzylorda region. In particular, on the basis of this work the author considers the level of influence of organized crime environment for other prisoners and proposes measures to stop them.Key words: correctional institution, convicted, convicted negative orientation, criminal environment, traditions of the criminal environment, organized criminal group.